Padrões evolutivos de Zygothrica vittimaculosa Burla, 1956 (Diptera: Drosophilidae) no Brasil, com identificação e descrição de uma espécie-irmã - Fonseca, Pedro Mesquita (2015)
The epoch of Pleistocene was marked by grate climate and flora alterations. On the southern hemisphere, where the glaciations had less intensity, there was the formation of refuges, providing a favorable condition to speciation. The genus Zygothrica (Diptera: Drosophilidae) is characterized by their interaction with fungi. Zygothrica vittimaculosa is considered a generalist species, because it explores even fungi, flowers (genus Cestrum, Solanaceae) and rotting fruits. In this work we identified a new species that is cryptic with Z. vittimaculosa and they are simpatric in almost all distribution area. However, this new species is rarely collected in resources but Cestrum inflorescences, differently of Z. vittimaculosa. Only after molecular analyses we realize it was a new species (posteriorly confirmed by male internal genitalia analyses), due to the external morphology of both species is identical. Also in this work we did the taxonomic description of this new species. A comparative analysis was performed by photographs, with the documentation of the external patterns (morphology and color) and the internal genitalia morphology (considered diagnostic) for both females and males, in addition to a measures table. Finally, was also performed a phylogeographic study based on two mitochondrial markers: COI (Citochrome c Subunit I) and COII (Citochrome c Subunit II). In this case, through collections and climate variables data, we estimate the present distribution of both species as well as an estimated of the Last Glacial Maximum distribution (about 20,000 years), suggesting that the potential distribution of both species seems to be restricted to the already sampled area, besides pointed a high suitability in northern Peru and western Chile for the new species, data not inferred to Z. vittimaculosa. About phylogeographic patterns, we suggest that, through Neutrality tests and Diversity indexes, the newest species had a really recent expansion, and potentially is also in diversification and expansion, while Z. vittimaculosa, despite also presents population expansion signals, these are less intense than their sister-species. To explain this inference, we can assume that because Z. vittimaculosa be more generalist than the other species, it had suffered more selection pressure, diversifying and increasing the number of haplotypes.